The potential significance of tempering treatment in alleviating the hydrogen embrittlement susceptibility of a hot-rolled and intercritically annealed medium-Mn steel. (January 2021) - Zhao, Xiaoli; Zhang, Yongjian; Hui, Weijing; Shao, Chengwei; Wang, Cunyu; Dong, Han
Highlights: Effect tempering on Hydrogen embrittlement (HE) of medium Mn steel was evaluated. Tempering has significant positive effect on the HE behavior of medium Mn steel. Enhanced HE resistance is primarily due to microstructural change during tempering. A novel strategy combined with sheet surface protection treatment is proposed. Abstract: The influence of tempering on the hydrogen embrittlement (HE) behavior of a hot-rolled and intercritically annealed medium-Mn steel (0.1C-5Mn) was investigated by slow strain rate tensile testing. It was observed that the absorbed diffusible hydrogen content remained almost unchanged with increasing tempering temperature. The susceptibility to HE evaluated by the relative total elongation loss is most significant for the as-annealed specimen, while tempering treatment can notably alleviate it. It is nearly immune to HE when the tempering temperature was increased up to 500 °C. The fraction of hydrogen-induced brittle fracture decreases with increasing tempering temperature. The enhanced resistance to HE of the tested steel is primarily ascribed to the microstructural evolution of retained austenite and cementite during the tempering process. It is thus proposed that the HE susceptibility of medium-Mn steel could be significantly reduced through suitable tempering treatment after intercritical annealing provided no notable loss of its superior strength-ductility balance.